Efficacy of new generation herbicides for weed management in dry direct seeded system of rice - Arya, S.R.; Ameena, M. (Annals of Agricultural Research, 2017)
The present study was conducted during kharif season of May to September 2014 to evaluate theweed control efficiency of low dose new generation herbicides in semi dry system of ricecultivation.Results of the study revealed substantial reduction in weed population and biomass in all theherbicide treated plots compared to weedy check. Pre-emergent herbicide application followed byeither hand weeding at 40 DAS or application of post emergent herbicides recorded higher weedcontrol efficiency in comparison with hand weeding twice (20 and 40 DAS). Bensulfuron methyl +pretilachlor @ 60 + 600 g ha–1 and pyrazosulfuron ethyl @ 25 g ha–1 were found promising broadspectrum herbicides for early season weed control in semi dry system of rice cultivation. Handweeding at 20 and 40 DAS (T10) recorded lowest weed density, weed dry weight and highest weedcontrol efficiency. Hence pre-emergence application of either bensulfuron methyl + pretilachlor @60 + 600 g ha–1 or pyrazosulfuron ethyl @ 25 g ha–1 on the next day of sowing followed by postemergence application of azimsulfuron @ 30 g ha–1 at 25 DAS could be recommended as the mosteffective weed management practice for dry direct seeded system of rice.